2013
DOI: 10.1002/ajmg.a.36291
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel candidate gene loci and increased sex chromosome aneuploidy among infants with conotruncal heart defects

Abstract: Congenital heart defects are common malformations, affecting 4–8 per 1,000 total births. Conotruncal defects are an important pathogenetic subset of congenital heart defects, comprising nearly 20 percent of the total. Although both environmental and genetic factors are known to contribute to the occurrence of conotruncal defects, the causes remain unknown for most. To identify novel candidate genes/loci, we used array comparative genomic hybridization to detect chromosomal microdeletions/duplications. From a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Previous studies have shown the association between the deleted genes and phenotype in 10q22.3–q23.3 deletion [van Bon et al, ]. Specifically the role of the BMPR1A gene in the cardiac defects has been suggested [Breckpot et al, ; Osoegawa et al, ]. In this study, we describe a new case with microcephaly, cardiac defect, mild intellectual disability, and multiple congenital anomalies in which a de novo interstitial 8.2‐Mb duplication of chromosome region 10q22.3–q23.3 containing BMPR1A and NGR3 was identified by Illumina SNP array analysis.…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies have shown the association between the deleted genes and phenotype in 10q22.3–q23.3 deletion [van Bon et al, ]. Specifically the role of the BMPR1A gene in the cardiac defects has been suggested [Breckpot et al, ; Osoegawa et al, ]. In this study, we describe a new case with microcephaly, cardiac defect, mild intellectual disability, and multiple congenital anomalies in which a de novo interstitial 8.2‐Mb duplication of chromosome region 10q22.3–q23.3 containing BMPR1A and NGR3 was identified by Illumina SNP array analysis.…”
Section: Introductionmentioning
confidence: 63%
“…Schematic representation of the studied 22q11.2 region from the most centromeric 18.2 Mb to the 22.7 Mb position. The figure displays, from top to bottom: scale of locus and assembly, chromosome 22 position by UCSC genome browser hg38, LCR22 blocks, typical and distal deletion intervals, 22q11.2 atypical deletion patients reported in the literature [D'Angelo et al, ; Garcia‐Minaur et al, ; Michaelovsky et al, ; Osoegawa et al, ; Rump et al, ; Verhagen et al, ], LCR22‐C to D/E deletion patients discussed in this report, RefSeq genes, and Segmental Duplications reported by UCSC (a blue shadow remarks the genes included in the deletion detected in our patients and an orange box remarks the duplication blocks included in the distal breakpoint region).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, deletions involving any of the two LCRs from D to H, known as distal deletions, are associated with a variable and relatively mild phenotype, with growth delay of prenatal onset [Rauch et al, , ; Ben‐Shachar et al, ; Tan et al, ; Fagerberg et al, ; Mikhail et al, ]. A limited number of patients with deletions involving other LCRs have also been reported and they are frequently called atypical deletions [Garcia‐Minaur et al, ; D'Angelo et al, ; Michaelovsky et al, ; Verhagen et al, ; Molck et al, ; Osoegawa et al, ; Rump et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…He is non‐syndromic with a complex heart defect including coarctation of the aorta, a VSD, parachute mitral valve and transverse hypoplasia. Duplication of GATA4 is an established cause of conotruncal and septal heart defects with variable penetrance in 8p23.1 DS [Joziasse et al, ; Barber et al, ], and a further infant with isolated Tetralogy of Fallot (TOF) and a full 8p23.1 duplication was recently ascertained among 290 infants with TOF from 974,579 births in the California Study of Birth Defects Causes [Osoegawa et al, , Subject C]. A large microduplication including SOX7 and GATA4 was recently found in another nonsyndromic patient with bicuspid aortic valve and aortic regurgitation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 8p23.1 duplication syndrome (8p23.1DS) is the reciprocal of the 8p23.1 deletion syndrome and a relatively rare genomic condition with an estimated prevalence of 1 in 58,000 [Barber et al, ]. Using molecular cytogenetic methods, the full 8p23.1DS has been confirmed in twenty‐four reported patients of whom nineteen were probands and five were other family members [Barber et al, , , ; Yu et al, , ; Longoni et al, , Patient 3; Barber et al, ; Osoegawa et al, , Subject C]. The 8p23.1 DS has a variable phenotype with the three relatively common features of developmental delay and/or learning difficulties, congenital heart disease (CHD) and a degree of mild dysmorphism that may be minimal [Yu et al, ; Barber et al, ]; other phenotypic features include behavioral problems, cleft lip and/or palate, macrocephaly, seizures, attention deficit hyperactivity disorder (ADHD), ocular anomalies, balance problems, hypotonia, hydrocele [Barber et al, , , ; Yu et al, , ] and, on one occasion, congenital diaphragmatic hernia (CDH) [Longoni et al, , Patient 3].…”
Section: Introductionmentioning
confidence: 99%